An Analysis of Brazilian Symposium on Software Quality (SBQS): Retrospective, Relevance, and Trends in the Past 5 Years - Freire, Emmanuel Sávio Silva; Cedro, Daniela Medeiros; Serra, Antonio de Barros (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
The Brazilian Symposium on Software Quality (SBQS, the acronym in Portuguese) is the main Brazilian forum dedicated exclusively to the exchange of experiences between the academia and the industry about quality software practice. In this year 2018, the SBQS holds its seventeenth edition. In this sense, this paper aims to analyze the technical works and the reports of experience of the last five editions of the event. Therefore, a scoping study was carried out considering the SBQS proceedings published between the years 2013 and 2017. Thus, the institutions (education and industry) that were published together were identified and quantified along with the total publication by state and by researcher. Moreover, the results obtained by the present research were compared with the investigation carried out between the years 2008 and 2012 that also performed a systematic literature review in the proceedings of referred event. As results, it was found that the symposium should encourage the publications in English language, the international cooperation, and the cooperation between academia and industry in technical works.